2022
DOI: 10.1002/ps.6806
|View full text |Cite
|
Sign up to set email alerts
|

Recently introducedWolbachiareduces bacterial species richness and reshapes bacterial community structure inNilaparvata lugens

Abstract: BACKGROUND Wolbachia has been developed as an effective tool to suppress insect pests and arbovirus transmission. Recently, the brown planthopper Nilaparvata lugens, a serious agricultural pest, has been successfully transinfected with Wolbachia wStri strain from Laodelphax striatellus. However, before conducting the field experiments, the impacts of wStri on the bacterial microbiota in N. lugens and how it differs from native Wolbachia wLug strain have not been clarified. RESULTS Here, we found that wStri red… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 71 publications
0
3
0
Order By: Relevance
“…On the other hand, our previous study suggested that leaf miners may acquire some microbes from the surrounding environment, including host plants or soil ( Zhu et al, 2022a ). The interaction between microbes also impacts the host microbiome ( Itoh et al, 2019 ; Li et al, 2022a , b ). We thus suggest that not only deterministic processes (e.g., host, environment), but also stochastic processes govern microbiota variation from wild to captive.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, our previous study suggested that leaf miners may acquire some microbes from the surrounding environment, including host plants or soil ( Zhu et al, 2022a ). The interaction between microbes also impacts the host microbiome ( Itoh et al, 2019 ; Li et al, 2022a , b ). We thus suggest that not only deterministic processes (e.g., host, environment), but also stochastic processes govern microbiota variation from wild to captive.…”
Section: Discussionmentioning
confidence: 99%
“…These genes are abundant in plants and play a key role in plant defense by mediating signal transduction [ 59 ], whereas iron complex outer-membrane receptor protein, PTS system, and cellobiose-specific llC component were functionally enriched in larval, pupal, female, and male intestines. Iron complex outer-membrane receptor protein is important for signaling and cellular processes during the different developmental stages of insects [ 60 ]. The PTS system helps bacteria to maintain different sugar levels and is involved in carbon metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the readjusted daily signaling pattern in our study could be an associated adaption in order to manage the available nutrients more effectively. In addition, the nutritional role of intestinal bacteria in medfly [ 139 ] and the recently confirmed Wolbachia effects on the relative abundance of resident bacteria in mosquitoes [ 140 ], Drosophila [ 141 ], and planthoppers [ 142 , 143 ] set the ground to further investigate the interaction between Wolbachia and medfly gut microbiota and the impact of this interaction on nutrient utilization and/or metabolism. Moreover, there is evidence that the composition of the symbiotic microflora could affect C. capitata mating behavior.…”
Section: Discussionmentioning
confidence: 99%